MIRA Rehab: a tale of hi-tech physiotherapy - Mihaiu, Cosmin (Henry Stewart Talks, 2017)
Traditional physiotherapy, MIRA Rehab, Physiotherapy by video-games, Microsoft Imagine Cup, Building a business, Connecting with clinicians, Developing a business model, Personal development